2018
DOI: 10.1016/j.jacc.2018.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Association of Assisted Reproductive Technologies With Arterial Hypertension During Adolescence

Abstract: ART-induced premature vascular aging persists in apparently healthy adolescents and young adults without any other detectable classical cardiovascular risk factors and progresses to arterial hypertension. (Vascular Dysfunction in Offspring of Assisted Reproduction Technologies; NCT00837642.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 42 publications
4
76
2
2
Order By: Relevance
“…Many human assisted reproductive techniques occur either in seminal plasma-free environments and/or where embryos are transferred into a uterine environment that has not been primed by seminal plasma. Indeed, studies are now identifying significant changes in cardiometabolic health of children derived from assisted reproductive techniques (Meister et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many human assisted reproductive techniques occur either in seminal plasma-free environments and/or where embryos are transferred into a uterine environment that has not been primed by seminal plasma. Indeed, studies are now identifying significant changes in cardiometabolic health of children derived from assisted reproductive techniques (Meister et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al studied more than 210,000 children born in Western Australia between 1994 and 2002 and found an increased risk of intellectual disability for children conceived by ART (10). Researchers also reported an increase in arterial hypertension in children conceived by ART, probably due to ART-induced premature vascular aging (13,14). Fetus conceived by ART also showed signs of cardiovascular remodeling, including a more globular heart, thick myocardial walls, decreased longitudinal functions, impaired relaxation, and dilated atria (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although the overwhelming number of children born with the aid of ART and NIFT are healthy and developing normally, reports of potential increases in the incidence of premature birth, low birth weight, congenital abnormalities, and imprinting disorders in the ART group are concerning . Increasingly, data suggest that children born with ART are at greater risk of developing adult onset cardiovascular dysfunction, including premature atherosclerosis, systemic hypertension, the persistence of fetal cardiovascular remodeling, vascular endothelial dysfunction, and exaggerated hypoxic pulmonary vasoconstriction . For example, a few studies that included small numbers have shown that children conceived via ART have systemic vascular endothelial dysfunction, as demonstrated by selective impairment of endothelium‐dependent vasodilation utilizing flow‐mediated dilation, increased carotid artery stiffness with intima‐medial hypertrophy, and increased systemic blood pressure .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Increasingly, data suggest that children born with ART are at greater risk of developing adult onset cardiovascular dysfunction, including premature atherosclerosis, systemic hypertension, the persistence of fetal cardiovascular remodeling, vascular endothelial dysfunction, and exaggerated hypoxic pulmonary vasoconstriction. 5,[9][10][11][12] For example, a few studies that included small numbers have shown that children conceived via ART have systemic vascular endothelial dysfunction, as demonstrated by selective impairment of endothelium-dependent vasodilation utilizing flowmediated dilation, increased carotid artery stiffness with intimamedial hypertrophy, and increased systemic blood pressure. 9,12 Importantly, compared to age-matched controls, healthy children conceived via ART display an exaggerated hypoxic pulmonary vasoconstricting response at altitude, that is associated with right ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation